2021
DOI: 10.3390/ijerph18041629
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Changes in Saliva in Radiotherapy-Induced Head Neck Cancer Patients

Abstract: The intact function of the salivary glands is of utmost importance for oral health. During radiotherapy in patients with head and neck tumors, the salivary glands can be damaged, causing the composition of saliva to change. This leads to xerostomia, which is a primary contributor to oral mucositis. Medications used for protective or palliative treatment often show poor efficacy as radiation-induced changes in the physico-chemical properties of saliva are not well understood. To improve treatment options, this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 74 publications
0
26
0
2
Order By: Relevance
“…Therefore, topical administration of drug candidates directly to the oral mucosa is a promising strategy to achieve a fast therapeutic local effect and avoid additional side effects. In medication development, however, many studies do not take into account the changes in the barrier systems in the mouth caused, for example, by pro-inflammatory cytokines [ 45 ]. Accordingly, the potential of local drug delivery systems to transport the active ingredient to the site of action is often limited.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, topical administration of drug candidates directly to the oral mucosa is a promising strategy to achieve a fast therapeutic local effect and avoid additional side effects. In medication development, however, many studies do not take into account the changes in the barrier systems in the mouth caused, for example, by pro-inflammatory cytokines [ 45 ]. Accordingly, the potential of local drug delivery systems to transport the active ingredient to the site of action is often limited.…”
Section: Discussionmentioning
confidence: 99%
“…When unstimulated saliva was analysed using Cryo-SEM, the mucin networks seen in saliva from healthy persons was not present in saliva from patients who had undergone radiation therapy of the head and neck region [ 44 ]. Preliminary results from microscope analysis of stimulated saliva from our head and neck cancer patients show a similar pattern with a lower degree of networks compared with stimulated saliva from healthy persons with normal salivary secretion rate.…”
Section: Discussionmentioning
confidence: 99%
“…Gel might be one of most convenient agents for application in a limited and irregular space, such as the intrauterine space, and most gel agents commonly contain derivatives of hyaluronic acid (HA) with other main components, such as sodium D-glucuronate and N-acetyl-glucosamine, which is a linear polysaccharide with 25,000 repeating disaccharide units, composed of major supportive and protective components in a vitreous body, saliva, synovial fluid, cartilage, skin, and umbilical cord [157][158][159][160][161][162][163]. Earlier reports have shown that the application of CHA gel has reduced the severity of postoperative IUA after hysteroscopic procedures [86,109,111,112].…”
Section: Gels As Anti-adhesive Agentsmentioning
confidence: 99%